C1q Confers Protection Against Cryptococcal Lung Infection by Alleviating Inflammation and Reducing Cryptococcal Virulence. (21st March 2023) - Zhao, Xu; Shen, Lei; Zheng, Jianming; Zhu, Haiyan; Li, Li; Shi, Hong; Chen, Zhongqing; Li, Qian
Abstract: Background: To define the role of C1qa in host defense against Cryptococcus neoformans lung infection, we investigated its susceptibility to cryptococcal lung infection in mice deficient in complement factor C1qa ( C1qa −/− ). Methods: We established a wild-type (WT) and C1qa-deficient murine inhalation model with C. neoformans . We compared the host survival rate, inflammatory responses, and pathogenicity of C. neoformans during the infection course between WT and C1qa −/− mice. Results: The mortality rate of C1qa-deficient mice was significantly higher than that of wild-type mice. The increased formation of Titan cells in the lungs was associated with augmented inflammation in C1qa-deficient mice. The capacity of lung homogenate supernatant from C1qa-deficient mice to induce Titan formation in vitro was greater compared with that of wild-type mice. The C. neoformans isolated from the lungs of infected C1qa-deficient mice was more resistant to macrophage killing in vitro and caused significantly higher mortality after administration to mice compared with that isolated from WT mice. Conclusions: These findings reveal a novel role of C1qa in host defense against C. neoformans infection by regulating host inflammation and pathogen virulence and provide new insight into the C1q-mediated lung environment underlying the transition from yeast to Titan cell.